2017
DOI: 10.3390/met7040120
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Characterization of Powder Mixture Including a Space Holder and Its Application to Metal Injection Molding

Abstract: Abstract:Metal injection molding (MIM) with the space holder technique is becoming one of the important fabrication methods for a net-shape production of micro-sized, porous, complex-shaped metal parts. For a successful injection molding step, rheological behavior of MIM feedstock is essential, which includes peculiar characteristics, such as a wall slip phenomenon. SUS 316L stainless steel powder, binder systems (paraffin wax, polypropylene, polyethylene, stearic acid) and three different sizes of spherically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This material is commonly used in the chemical industries and marine industries [3][4][5]. In order to decrease the cost for post-processing, 316L SS has been produced by many advanced net shape fabrication technologies, including selective laser melting (SLM) [6], and metal injection molding (MIM) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This material is commonly used in the chemical industries and marine industries [3][4][5]. In order to decrease the cost for post-processing, 316L SS has been produced by many advanced net shape fabrication technologies, including selective laser melting (SLM) [6], and metal injection molding (MIM) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Metal injection molding of 316L SS is an attractive net shape fabrication method due to its capability of mass production of parts with complex shapes [7][8][9], which has been extensively investigated by many researchers. The effect of debinding temperatures on the microstructure and mechanical properties of 316L SS was investigated by Amin et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…The difference between the CPVC value of the 316L in this study and related studies, using similar PSD, which reported values close to 66% [7,14,17,19], can be attributed to the use of different binder type or processing conditions (mixing temperature or speed). The influence of these differences is seen in a related study in which a CPVC of 61% was reported for a 316L stainless-steel powder [20].…”
Section: Optimization Process: Effects Of Powder Typementioning
confidence: 91%
“…3 The parts have high precision, excellent mechanical properties, large-scale, fast and efficient production, and it has been applied in many fields. 4,5,6 A key problem in MIM is how to improve the shape retention or dimensional stability of the final product. This is the result of comprehensive factors, which are significantly affected not only by critical powder loading, feedstock uniformity, and rheological properties but also by the interface bonding strength between powder and binder and the mechanical strength of green parts.…”
Section: Introductionmentioning
confidence: 99%